PENGARUH KEDISIPLINAN DAN KETERAMPILAN TERHADAP KINERJA KARYAWAN ADMINISTRASI KOMUNIKASI DI BANDAR UDARA HALIM PERDANAKUSUMA - Immanuel Edgar Partoguan; Hodi Hodi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
One of the essential considerations in the aviation industry is the airport's air transportation system. Every employee involved in airport operations must correctly complete each division's tasks. If the employees cooperate well, this implementation will be successful. The purpose of this study is to ascertain how discipline and expertise affect the performance of airport communications administration staff. Sampling using a purposive sampling technique. The research data was obtained by distributing employee discipline, skills and performance questionnaires to 40 respondents. The data analysis technique used is multiple linear regression using the IBM SPSS Statistics 25 application. The results showed that discipline and skill combined contributed to employee performance by 84.2% and that the remaining 15.8% of employee performance was influenced by other factors not examined in this study.